The elite judo female athlete’s heart - Milovančev, Aleksandra; Petrović, Milovan; Miljković, Tatjana; Ilić, Aleksandra; Mudrinić, Tatjana Redžek; Miljković, Aleksandar; Ivanov, Olivera; Tripunović, Jelena; Anđelic, Bogdan; Bianco, Antonino; Drid, Patrik (Frontiers in Physiology, 2022)
Purpose: There is a paucity of data on physiological heart adaptation in elite-level judo female athletes. This study aimed to assess left ventricular morphology and function in highly trained elite female judokas. Methods: The study prospectively included 18 females aged 23.5 ± 2.25 years, 9 elite level judokas, and 9 healthy non-athlete volunteers. All participants underwent a medical examination, electrocardiogram, and transthoracic 2D echocardiogram. Various parameters of left heart morphology and function were measured and compared between groups. Results: When groups were compared, judokas had significantly increased left ventricular cavity dimensions p < 0.01, left ventricular wall thickness p < 0.01, and volumes p < 0.01. Elite female judokas exhibited left ventricular dilatation demonstrated as high prevalence increased end-diastolic volume/index, and increased end-systolic volume/index in 88.9% of judokas vs. 0% in controls, p < 0.01. Left ventricle mass/index was significantly increased in judokas, p < 0.01), with a 43.3% difference between groups. The majority (77.7%) of judokas had normal left ventricular geometry, although eccentric hypertrophy was revealed in 2 (22.2%) of judokas. Conclusion: Elite, highly trained female judokas exhibit significant changes in left heart morphology as a result of vigorous training when compared to non-athletes. These findings suggest that female judokas athletes' heart follows a pattern toward chamber dilatation rather than left ventricular wall hypertrophy.